A proposal for a mechanical solution for wheelchair transfers focusing on the demands of elderly users (Human Factors in Design, 2023)
The transfer maneuver is an activity performed in the routine of wheelchair users; however, many users may have difficulty doing it safely and independently. This work reports the development of a proposal to assist transfers, focusing on the needs of the elderly public. Based on an integrated methodology, users and health professionals are evaluated, studying discomfort when transferring from a wheelchair. As a result, a proposed solution for different types of wheelchairs is structured. The project contributed to helping the personal mobility of the elderly, addressing various transfer interfaces.
Keywords: wheelchair; eldery; transfer